Latvian action nouns with the suffix -iens: does the productivity of this word formation type increase? - Navickaitė-Klišauskienė, Agnė (Baltistica, 2022)
This research is an attempt to answer the question whether the word formation type of action nouns with the suffix -iens is productive in contemporary Latvian. The article is based on quantitative analysis of data in the Latvian corpus Tīmeklis 2020. Special attention is allocated to expanding productivity and hapax legomena – derivatives that occur only once in the corpus.
Keywords: Latvian; word-formation; action nouns; productivity; hapax legomena